SIM (Management Information System) in Organizations - Maura Diva Muchlisa Yapant; Cutifa safitri (International Journal on Economics, Finance and Sustainable Development, 2021)
Many human activities related to information systems, whether consciously or not, information systems have helped humans a lot. It should be noted that information systems do not always have to be complex—simple information systems. The system is only used to record sales transactions involving one person only; through a computer, the user enters sales data, and when the store is closed, a daily sales report is printed. Furthermore, the report is used to analyze salable items that are useful for making purchasing decisions. A management information system is a comprehensive, coordinated, and rationally integrated set of information sub-systems capable of transforming data into information through a series of ways to increase productivity by the style and nature of managers based on predetermined quality criteria. The development of a sophisticated computer-based MIS requires several highly skilled and long-experienced people and requires the participation of organizational managers.